AL-TURĀṠ WA AL-TAJDĪD: UPAYA PEMBAHARUAN HASSAN HANAFI DAN RELEVANSINYA DALAM KONTEKS KE INDONESIAAN - Yuslih, Muhammad Yuslih; Ain, Aiyuhan Nurul (Mazalat: Jurnal Pemikiran Islam, 2024)
In the intellectual khazanh of Islam, Hasan Hanafi is one of the leading figures of Islamic reform with the idea of Turāṡ Wa Al-Tajdīd. Hasan Hanafi's idea of renewal is intended for Muslims to develop a progressive vision of life through the dimension of liberation. Therefore, this paper aims to see the big idea of Hasan Hanafi's renewal and how relevant it is in the context of Indonesia. This research is included in the type of literature research whose data is obtained from various books, journals, papers, related to this research. The data in this study is divided into two, namely primary and secondary data. Primary data comes from books written directly by Hasan Hanafi and secondary data is a variety of books, journals, which can support this paper. After the data collected, the analysis was carried out with Miles and Hubermas models. The results of this study show that in an effort to realize the revival of the Islamic Revolution, and the unity of the Ummah, Hassan Hanafi built a civilization project called “tradition and modernity” (Turāṡ Wa Al-Tajdīd). In short, it can be said that the Islamic left is based on three pillars in order to realize the revival of Islam, the Islamic Revolution, and the unity of the people. First, the revitalization of classical Islamic treasures. Second, against Western civilization. Third, the analysis of the reality of the Islamic world. Hassan Hanafi's ideas about at-turatats wa at-tajdīd can be applied in Indonesia in order to overcome poverty as a chronic social problem. The proposed effort is to increase the participation of individuals and the private sector in this case the business world to more actively help and improve the quality of life of disadvantaged communities. The activity of individuals and the private sector in poverty alleviation is an important aspect that will help government programs in overcoming poverty.